Pengaruh Penggunaan Sari Wortel Terhadap Kualitas Donat - BR Sinuhaji, Sri Ulina; Ruaida, Ruaida; Yuliana, Yuliana (Journal of Home Economics and Tourism, 2014)
This research aims to analyze the differences in the effect of the use ofexternal quality carrot juice to cover the volume, color, shape, texture smooth,soft textur, aroma, sweetness, flavor carrot, and hedonic on donuts. This researchis an experiment using a completely randomized design of three replications / trialwith the number 30 panelists. The independent variable was the use of carrotjuice (X) and the dependent variable (Y) is the quality donuts covers of eachquality. Based on the analysis of the results of the study showed that the quality ofthe test volume levels obtained volume expands categorized, categorized goldenyellow color, round shape simestris categorized, categorized smooth texturesmooth, soft texture soft category, aroma scent category carrots, sweet taste of thesweet and was carrots. Based on the data of all tests performed significantly Hawhich reads thus there is a difference in the effect of all studied quality.Keywords: influence, juice carrot, quality doughnuts